2018
DOI: 10.1186/s12909-018-1300-5
|View full text |Cite
|
Sign up to set email alerts
|

A study of resident duty hours and burnout in a sample of Saudi residents

Abstract: BackgroundWork hour restrictions in residency programs have been implemented over the last several decades in Europe, USA, and Canada. To best of our knowledge, there is no study of resident duty hours in the Kingdom of Saudi Arabia. In addition, few studies have looked at the prevalence of burnout amongst Saudi residents. The present study explored resident duty hours and burnout amongst residents in Saudi Arabia.MethodsA paper-based questionnaire was designed to survey resident duty hours in Saudi Arabia and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
40
2
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 22 publications
8
40
2
3
Order By: Relevance
“…Although Contag et al 28 reported that the number of working hours was not associated with the rate of burnout, in the present study, residents were more burned out due to long working hours (P = 0.003). Furthermore, Hameed et al 29 conducted a similar study and explored the relationship between duty hours and burnout among medical residents in Saudi Arabia. They found a very high degree of burnout among medical residents, which supports the findings in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Although Contag et al 28 reported that the number of working hours was not associated with the rate of burnout, in the present study, residents were more burned out due to long working hours (P = 0.003). Furthermore, Hameed et al 29 conducted a similar study and explored the relationship between duty hours and burnout among medical residents in Saudi Arabia. They found a very high degree of burnout among medical residents, which supports the findings in this study.…”
Section: Discussionmentioning
confidence: 99%
“…24 Hameed et al (2018) study was the first to describe residents' duty hours by surveying Saudi medical and surgical residency programs at three training centers, and it found 50% working 60-79 hours while 30% worked 80-plus hours per week. 25 The impact of the 80-hour resident workweek on both surgical residents and attending surgeons has been examined, 26 with residents' quality of life found to improve after work-hour changes. As documented by the Accreditation Council for Graduate Medical Education (ACGME) surgical case logs, the PGY5 increased their case volume, while all other residents maintained the same case volume despite the reduction in work hours.…”
Section: Preparedness For Examsmentioning
confidence: 99%
“…Other than this, Barrack et al found that resident duty hour limitation can have a positive impact on reducing burnout among orthopaedic surgery residents 36 . However, this is still controversial as various other studies describe that duty hour limitations did not influence burnout 26,37 . Only a longitudinal study on a larger group of residents can answer these questions regarding the best strategy to be adapted to overcome resident burnout.…”
Section: Discussionmentioning
confidence: 93%